Impactos distributivos da educaç\~ao pública no Brasil ao longo do século XXI - Fernando Gaiger Silveira; Theo Ribas Palomo; Adriano Souza Senkevics; Matias Cardomingo; Laura Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This text investigates the impacts of education's public spending on social inequality in Brazil throughout the 21st century. For that, two data sources were used: the last three editions of the IBGE's Consumer Expenditure Survey (POF), referring to the years 2002-2003, 2007-2008 and 2017-2018, and the investment per student calculated by Inep. In addition, the study presents a methodological innovation by comparing these data from Inep with information on non-monetary expenditures on education estimated by the interviewees in POF, published in an unprecedented way in the latest edition of the survey. In this way, it was possible to reconstruct family income before and after transfers via public education and their redistributive impacts on the Gini index. The results indicate high progressivity of public educational expenditure: between 62.0% and 65.5% of the expenditure goes to the bottom 50%, who appropriate only 14.3% of monetary income; on the other hand, the top 10% of the population represent 45.2% of monetary income, but their share of public spending is between 5.8% and 6.7%. Furthermore, when analyzing the impact of each education level on inequality, it is possible to note that the greatest progressive impact resides on elementary education, whereas higher education is the only one that has a regressive impact. Overall, the redistributive impact of public education spending on inequality represents a reduction in the Gini Index between 5.3%, based on POF data, and 9.6%, based on Inep data. In comparative terms, in the first two decades of the 21st century, the public spending in education increased its progressivity: the share of these expenditures in the family income moved from 7.2% in 2002-2003 to 8% in 2008-2009 and 2017-2018, and the concentration coefficient was significantly reduced, which is largely the result of the advance of universal access and the democratization of educational opportunities.
10419/284881
Keywords: 330; education spending; fiscal incidence; inequality